1991
DOI: 10.1080/11250009109355778
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme versus discrete morphologic characters in the phylogenetic analysis of the land snailSolatopupa(Pulmonata, Chondrinidae)

Abstract: In the six species of Solatopupa, genetic information apparently disagrees with the taxonomic relationships already inferred from classical comparative analysis of shell morphology; a global reexamination of data in a phylogenetic perspective is therefore required. Different criteria of phylogenetic inference were applied to allozyme data from previous studies (28 loci) and to a matrix of 17 binary factors descriptive of morphological characters (shell and genital anatomy) with the purpose of making a comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 34 publications
0
17
1
Order By: Relevance
“…Boato (1986) demonstrated an allopatric distribution of populations of S. similis with diVerent chromosome numbers (2N D 60 in populations from Spain to Western Liguria, 2N D 58 in populations from Eastern Liguria to Northern Latium). Subsequently, the same author found more than a 40% of genetic divergence at 28 allozyme loci and slight morphological diVerences between the two chro-mosomal forms (Boato, 1988(Boato, , 1991. On these bases, Eastern populations of S. similis with 2N D 58 were attributed to S. juliana.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Boato (1986) demonstrated an allopatric distribution of populations of S. similis with diVerent chromosome numbers (2N D 60 in populations from Spain to Western Liguria, 2N D 58 in populations from Eastern Liguria to Northern Latium). Subsequently, the same author found more than a 40% of genetic divergence at 28 allozyme loci and slight morphological diVerences between the two chro-mosomal forms (Boato, 1988(Boato, , 1991. On these bases, Eastern populations of S. similis with 2N D 58 were attributed to S. juliana.…”
Section: Introductionmentioning
confidence: 96%
“…On these bases, Eastern populations of S. similis with 2N D 58 were attributed to S. juliana. In addition, previous phylogenetic hypotheses are available for the whole genus, based on morphology, allozymes, and karyology (Boato, 1986(Boato, , 1988(Boato, , 1991Gittenberger, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of evidence for that, however, we conclude that all available information should form the basis for the estimation of the evolutionary history. This interpretation is also supported by the incongruence test, which showed that only 5 of the total 28 character matrices yielded signi cant (at the 5% level) length differences between trees from soft and shell characters respectively: Boato (1991), Roth (1991Roth ( , 1996, Jensen (1996b), andWise (1996).…”
Section: Resultsmentioning
confidence: 69%
“…Ecological and behavioral characters, as well as characters of the radula and operculum, are referred to as "other". Molecular data from Rosenberg (1996) and data on diploid chromosome number from Boato (1991) were also included in the latter category. This category of characters was included in the phylogeny reconstruction to make it as reliable as possible (total evidence, in accord with, e.g., Kluge [1989]), but we have not tested this category against shell and soft-part characters because it is such a heterogeneous assemblage of character types.…”
Section: Resultsmentioning
confidence: 99%